Abuse of Narcotic Drugs in Swiss Criminal Law - Jovašević, Dragan (Zbornik Instituta za kriminološka i sociološka istraživanja, 2016)
Based on international standards which were adopted within the United Nations, all national legislation recognises different forms of manifestations of criminal offences of abuse of narcotic drugs. This paper discusses different activities of illegal production, trade and incitement or enabling other individuals to possess narcotic drugs in order to ingest them, which leads to endangering health or even life. Types of crime vary depending on the needs of every specific country, and different types of punishments and criminal sanctions are stipulated for the perpetrators. The situation is similar in the Federal Republic of Switzerland. This paper analyses the system of criminal offences in different forms and ways of manifestation in a theoretical and practical sense.